Clinical validation of a gene expression signature that differentiates benign nevi from malignant melanoma. (13th April 2015) - Clarke, Loren E.; Warf, B.M.; Flake, Darl D.; Hartman, Anne‐Renee; Tahan, Steven; Shea, Christopher R.; Gerami, Pedram; Messina, Jane; Florell, Scott R.; Wenstrup, Richard J.; Rushton, Kristen; Roundy, Kirstin M.; et al.
<x xml:space="preserve">Abstract</x> Background Histopathologic examination is sometimes inadequate for accurate and reproducible diagnosis of certain melanocytic neoplasms. As a result, more sophisticated and objective methods have been sought. The goal of this study was to identify a gene expression signature that reliably differentiated benign and malignant melanocytic lesions and evaluate its potential clinical applicability. Herein, we describe the development of a gene expression signature and its clinical validation using multiple independent cohorts of melanocytic lesions representing a broad spectrum of histopathologic subtypes. Methods Using quantitative reverse‐transcription polymerase chain reaction (PCR) on a selected set of 23 differentially expressed genes, and by applying a threshold value and weighting algorithm, we developed a gene expression signature that produced a score that differentiated benign nevi from malignant melanomas. Results The gene expression signature classified melanocytic lesions as benign or malignant with a sensitivity of 89% and a specificity of 93% in a training cohort of 464 samples. The signature was validated in an independent clinical cohort of 437 samples, with a sensitivity of 90% and specificity of 91%. Conclusions The performance, objectivity, reliability and minimal tissue requirements of this test suggest that it could have clinical application as an adjunct to histopathology in the diagnosis of melanocytic neoplasms.